Child and adolescent obesity. Issue 8 (August 2021) - Chapman, Simon
Abstract: Obesity and overweight are a pandemic that has been building since the 1980s. The causes are multi-factorial, and the solutions are ultimately political. The consequences, however, are medical. Admissions to hospital with obesity-related illness increased 4-fold between 2000 and 2009, and paediatricians regularly see comorbidities in their clinics and on their wards. Broaching the subject of obesity and overweight when we are talking to young people and their families is difficult. Detailed history and examination, in a systemic and non-judgemental way can identify these comorbidities so that they may be treated. Not to do so is a missed opportunity. Interdisciplinary working can support the child and their family to manage their weight. This article offers some personal experience and practical advice for health care professionals who want to make a real difference to the children in their care.